simplify the product (4-x)(x+9)

(4 - x)(x + 9) = 4x + 36 - x^2 - 9x = -x^2 - 5x + 36

Question

Asked 1/25/2013 9:12:09 PM

Updated 7/7/2014 6:32:45 PM

1 Answer/Comment

s

Rating

8

(4 - x)(x + 9) = 4x + 36 - x^2 - 9x = -x^2 - 5x + 36

Added 7/7/2014 6:32:45 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/7/2014 6:34:14 PM]

(x+6) (x+9) simplify **Weegy:** that's not possible! what do you need to know. [s] **User:** Name the binomial you can multiply by (x + 9) to get the product (More)

Question

Updated 8/18/2014 8:22:14 AM

1 Answer/Comment

(x+6)(x+9)

=(x+6)(x+9)

=(x)(x)+(x)(9)+(6)(x)+(6)(9)

=x^2+9x+6x+54

=x^2+15x+54

=(x+6)(x+9)

=(x)(x)+(x)(9)+(6)(x)+(6)(9)

=x^2+9x+6x+54

=x^2+15x+54

Added 8/18/2014 8:22:13 AM

This answer has been confirmed as correct and helpful.

simplify the product. (x-4)(x+3) **Weegy:** (x-4)(x+3) =
x2-12
**User:** Use the GCF of the terms to write the expression as the product of two factors with integer coefficients. -2x exponent 3 - 4x squared +4x **Weegy:** 2x(x2-2x+2) **User:** A rectangular box is twice as long as it is wide. The height of the box is 3 feet less than the width. If the box is x feet wide, what polynomial represents its volume in cubic feet? **Weegy:** The answer is: x=width of box. length of box = 2 * x. Height of box = x - 3.
Volume of box = length * width * height = 2x * x * (x-3) = 2x^2 * (x-3) = 2x^3 - 6x^2 **User:** A rectangular box is x feet long and x feet wide. The volume of the box is (4x^8+3x^6) cubic feet. What polynomial represents the height of the box in feet? **Weegy:** x = length of box, x= width of box. [ height of box = ?
Volume of box = length * width * height = 4x^8 + 3x^6.
Volume of box = length * width * height = x * x * height
x * x * height = 4x^8 + 3x^6
x^2 * height = 4x^8 + 3x^6
x^2 * height / x^2 = (4x^8 + 3x^6) / x^2
height = x^2 * (4x^6 + 3x^4) / x^2
height = 4x^6 + 3x^4. ] **User:** Suppose 3s represents an even integer. What polynomial represents the product of 3s, the even integer that comes just before 3s, and the even integer that comes just after 3s? **Weegy:** Informally, the greatest common divisor (GCD) of two polynomials and is the largest polynomial that divides both and evenly. [ The definition is modeled on the concept of the greatest common divisor of two integers, the greatest integer that divides both. For polynomials, the situation is slightly more complicated, because there is no canonical order which we can use to say which polynomial is "biggest." Instead, the GCD is chosen so its degree is as great as possible, and often so that its leading coefficient equals one (i.e., it is monic). The greatest common divisor is also sometimes referred to as the greatest common factor or the highest common factor. ] **User:** You have checked out b books from the library, where b is a number ... (More)

Question

Not Answered

Updated 6/25/2014 1:58:01 PM

3 Answers/Comments

(x-4)(x+3)

= x^2 + 3x - 4x - 12

= x^2 - x - 12

= x^2 + 3x - 4x - 12

= x^2 - x - 12

Added 6/25/2014 1:57:26 PM

This answer has been confirmed as correct and helpful.

2x(x^2-2x+2)

= 2x^3 - 4x^2 + 4x

= 2x^3 - 4x^2 + 4x

Added 6/25/2014 1:58:01 PM

This answer has been confirmed as correct and helpful.

34,013,347

questions answered

There are no comments.